Pembentukan Karakter Peserta Didik Melalui Pelajaran Pendidikan Al-Islam dan Kemuhammadiyahan di SD Muhammadiyah Toboali - Septia, Selviyana; Rudini, Rudini; Mahatma, Masmuni (LENTERNAL: Learning and Teaching Journal, 2023)
The problem in this study is to look at the character conditions among the educated today that do not reflect the education itself, so there is a need for an effort to shape the character of the student through character education that educates and guides towards a better direction with such complex challenges. Thus, through the teaching of Islam and the Prophet, it is hoped to improve the quality of the learning process and the learning outcomes of the students, so that they can produce agents of change who behave honestly and well in daily life without being made-made and ready to be generations of noble people.This type of research uses descriptive and qualitative research methods. The data collection methodology used is non-participatory observation, in which researchers are not directly involved in daily activities but rather through observation. Further data collection through structured interviews means that the researchers have prepared the guidelines for the interview in the form of written questions. Hasill's research suggests that there are several things that can shape the character of the student, namely, the methods of equality, cultivation, lecture, and integrity. These methods are used as a reference in order to form the character of a student who has extensive science and noble morality. In the implementation of character values through religious values, nationalist values, integrity, self-reliance, and gotong royong values.